Problems paying medical bills and mental health symptoms post-Affordable Care Act - Jacqueline C Wiltshire; Kimberly R Enard; Edlin Garcia Colato; Barbara Langland Orban (AIMS Public Health, 2020)
Healthcare affordability is a worry for many Americans. We examine whether the relationship between having problems paying medical bills and mental health problems changed as the Affordable Care Act (ACA) was implemented, which increased health insurance coverage. Data from the 2013–2016 Health Reform Monitoring Survey, a survey of Americans aged 18–64, were used. Using zero-inflated negative binomial regression, adjusted for predisposing, enabling, and need factors, we examined differences in days of mental health symptoms by problems paying medical bills (n = 85,430). From 2013 to 2016, the rates of uninsured and problems paying medical bills decreased from 15.1% to 9.0% and 22.0% to 18.6%, respectively. Having one or more days of mental health symptoms increased from 39.3% to 42.9%. Individuals who reported problems paying medical bills had more days of mental health symptoms (Beta = 0.133, p < 0.001) than those who did not have this problem. Insurance was not significantly associated with days of mental health symptoms. Over the 4-year period, there were not significant differences in days of mental health symptoms by problems paying medical bills or insurance status. Despite improvements in coverage, the relationship between problems paying medical bills and mental health symptoms was not modified.